Passive mode-locking of ytterbium-doped fiber laser using chemically exfoliated graphene as saturable absorber - Haris, Hazlihan; Arof, Hamzah; Harun, Sulaiman Wadi; Apsari, Retna (Old City Publishing, 2018)
An all-fiber passively mode-locked Ytterbium-doped fiber laser (YDFL) was demonstrated by using a chemically exfoliated graphene as saturable absorber (SA). The obtained graphene flakes were embedded into a PEO polymer to provide a modulation depth of 16.2 % and incorporated into an YDFL cavity to generate ultrafast fiber laser operating at 1052.9 nm. The laser generated stable soliton pulses with repetition rate of 4.5 MHz and the estimated minimum pulse width of 0.14 ps. The pulse energy of 1.5 nJ was obtained at the maximum pump power of 203.5 mW. This result indicates that the chemically exfoliated graphene is a promising means for mode-locked fiber lasers.